2016
DOI: 10.1111/jne.12345
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Effects of an Aggressive Interaction on Dehydroepiandrosterone, Testosterone and Oestradiol Levels in the Male Song Sparrow Brain: a Seasonal Comparison

Abstract: Across vertebrates, aggression is robustly expressed during the breeding season when circulating testosterone is elevated, and testosterone activates aggression either directly or after aromatisation into 17β-oestradiol (E2 ) in the brain. In some species, such as the song sparrow, aggressive behaviour is also expressed at high levels during the nonbreeding season, when circulating testosterone is non-detectable. At this time, the androgen precursor dehydroepiandrosterone (DHEA) is metabolised within the brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 54 publications
2
35
1
Order By: Relevance
“…2). DH E 2 levels were similar in absolute quantity to those reported in other studies of hippocampal and brain DH E 2 content in mice (Overk et al, 2013) and songbirds (Fokidis et al, 2015; Heimovics et al, 2016), although most studies, including the current study, focus on relative quantity of brain E 2 content between regions or time periods. These data suggest that letrozole suppresses an increase in DH E 2 levels 30 min after infusion at a dose shown to impair OR and OP memory consolidation in vivo .…”
Section: Resultssupporting
confidence: 81%
“…2). DH E 2 levels were similar in absolute quantity to those reported in other studies of hippocampal and brain DH E 2 content in mice (Overk et al, 2013) and songbirds (Fokidis et al, 2015; Heimovics et al, 2016), although most studies, including the current study, focus on relative quantity of brain E 2 content between regions or time periods. These data suggest that letrozole suppresses an increase in DH E 2 levels 30 min after infusion at a dose shown to impair OR and OP memory consolidation in vivo .…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, sparrows exhibit increased aromatase activity, an enzyme that converts T to E 2 , and increased ERα and ERβ mRNA expression in brain nuclei that regulate aggression ( 73 , 74 ). A more recent study confirmed that neural levels of DHEA, T, and E 2 are higher in brain tissue than in circulation and that a single STI event alone can induce localized changes in neural DHEA levels ( 75 ). Taken together, these data suggest that circulating DHEA is an important source of neurally-derived steroids and that DHEA metabolism in the brain stimulates territorial aggression during the non-breeding season of birds.…”
Section: Neurally-derived Steroid Synthesis In Other Speciesmentioning
confidence: 90%
“…Extensive evidence has been accumulated that the systems of local steroid synthesis exist in the organs other than gonads and adrenal since 1980s ( 1 , 2 ). Local production of steroids in the brain has been investigated in various vertebrates, including teleost fish ( 3 , 4 ), amphibia ( 5 7 ), birds ( 8 , 9 ), rodents ( 10 14 ), non-human primates, and humans ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%